2018
DOI: 10.1002/fsn3.813
|View full text |Cite
|
Sign up to set email alerts
|

What are the key factors influencing consumers’ preference and willingness to pay for meat products in EasternDRC?

Abstract: Dietary patterns for consumers among the elite and middle‐income classes in developing countries are shifting rapidly toward the consumption of more animal‐based products. Although this shift presents opportunities, there are significant market failures affecting their preferences and willingness to pay (WTP). This study used a multistage sample survey of 309 consumers from three different communities of Bukavu, Eastern DRC, to examine the effect of socioeconomic/socio‐demographic characteristics and quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 56 publications
1
34
1
2
Order By: Relevance
“…The results of the study are in line with those found by other authors: Udomkun et al (2018) in their study in Democratic Republic of Congo found that 53% of the respondents were dissatisfied with meat products in the market due to their high price, low quantity, unhealthiness, and harmful effects.…”
Section: Demand For Rabbit Productssupporting
confidence: 91%
“…The results of the study are in line with those found by other authors: Udomkun et al (2018) in their study in Democratic Republic of Congo found that 53% of the respondents were dissatisfied with meat products in the market due to their high price, low quantity, unhealthiness, and harmful effects.…”
Section: Demand For Rabbit Productssupporting
confidence: 91%
“…The average annual consumption of meat in developed countries is 75.5 kg/capita year, whereas consumption estimation in developing countries is of 33.9 kg/capita year. Worldwide, the levels of meat consumption are projected to increase by 72% in 2030 compared to the situation in 2000 (Fiala, 2008;Udomkun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the major food safety risks in China’s pork supply chain and the reality of the pork traceability system in China, this paper aims to study Chinese consumers’ preferences and willingness to pay (WTP) relating to animal welfare, lean meat essence test, traceability, and appearance attributes of pork products. There have been a lot of studies on consumers’ preference relating to traceability information [18,19,22,23,24,25,26,27,28,29,30], animal welfare [21,31,32,33,34,35,36,37], hormones or antibiotics [5,38,39,40,41,42], appearance [22,43,44,45,46,47,48], and other attributes of meat products in the United States, Britain, Germany, Spain, Australia, and other countries. In China, the largest developing country, due to the imbalanced economic and social development, the relative vastness of the region, the diversity of the food culture, and the complexity of the food safety issues, consumers’ preferences relating to the properties of meat products are specific to China.…”
Section: Introductionmentioning
confidence: 99%